CLINICAL AND AESTHETIC MANAGEMENT OF NATAL AND NEONATAL TEETH - Magda-Mihaela Luca; Malina Popa; Nicoleta Nikolajevic-Stoican; Roxana Buzatu; Bumbu Bogdan Andrei; Simina Boia (Romanian Journal of Oral Rehabilitation)
Natal teeth, a rare dental anomaly present in about 1 in every 2,000 to 3,500 live births, are teeth that are either present at birth (natal) or emerge within the first 30 days of life (neonatal). These teeth usually appear in the front lower jaw and can lead to issues such as breastfeeding challenges, tongue irritation, and a risk of aspiration. While most occurrences are isolated, some may be linked to syndromes. Management options vary and can include monitoring, smoothing, or extraction, depending on the case. All instances require evaluation by a pediatric dentist, and neonatal nurses should be trained to recognize and refer affected infants appropriately. Despite potential complications, proper management can relieve discomfort for both the infant and the mother. While they are primarily studied in terms of their clinical and pathological significance, their esthetic implications also warrant consideration. This paper reviews the esthetic concerns associated with these early-erupting teeth, including their morphology, impact on oral development, potential effects on future dentition, and the psychosocial influence on parents.